P65 Advanced neonatal nurse practitioner (ANNP) review of neonatal antibiotics in 36hours to improve antibiotics stewardship. Issue 9 (19th August 2020) - Bilkhoo, Charon; Gray, Jim; Patel, Mitul; Holder, Gemma; Perry, Michelle
Abstract : Aim: To ensure neonates in transitional care and postnatal wards are receiving antibiotics appropriately. NICE CG149 1 advises to consider stopping antibiotics at 36 hours in babies given antibiotics because of risk factors for infection or clinical indicators of possible infection where: the blood culture is negative, the levels and trends of C-reactive protein (crp) concentration are reassuring and no clinical indicators of possible infection Neonatal unit was excluded from this study; since daily clinician led ward rounds to review antibiotics already occur. Antibiotics not reviewed in the 36 hour time frame were due to delays in receiving the second crp level. Daily ward rounds to review antibiotics in neonates were not happening on transitional care and postnatal wards, thus to ensure regular care, advanced neonatal nurse practitioner led reviews were implemented. Method: A crp sample should be taken after delivery and in babies given antibiotics because of possible infection, the crp concentration is measured again 18–24 hours after presentation. The role of the ANNP is to ensure both crp levels are checked and the blood culture is negative, with the aim of stopping antibiotics at 36 hours before the second dose of gentamicin is due. In summary neonates that do not need antibiotics should have only had approximately 3 doses of benzylpenicillin and 1 dose of gentamicin. Audits were carried out on neonates in transitional care and postnatal wards who were receiving antibiotics. The initial base line audit was done over 3 months to assess if antibiotics were reviewed in 36 hours. This was deduced by a signature from the ANNP either stating on the drug chart that antibiotics would continue for 5 days until crp has decreased or the antibiotic would be discontinued if the crp was low. This audit was repeated a year later. Results: During the first 3 months audit the proportion of babies having their antibiotics reviewed within 36 hour time frame rose from 3% in month 1 to 25% and 50% in months 2 and 3 consecutively. During the second 3 month audit, the proportion of babies having their antibiotics reviewed was 78% in month 1 and 80% in the following two months. The first audit showed a rapid improvement, whereas the second audit showed an significant improvement compared to the end of the first audit, which was sustained throughout the full three months. Conclusion: The ANNP was a simple and no cost solution in ensuring antibiotic stewardship was consistent throughout neonates, reducing the length of stay of neonates and their mothers. The 20% of babies who are still not having a 36 hour review may be because of delays in blood cultures reaching the laboratories to commence incubation. Reference: Neonatal infection (early onset): antibiotics for prevention and treatment. NICE CCG149 2012.